Nanofiber-based Sm0.5Sr0.5Co0.2Fe0.8O3-δ/N-MWCNT composites as an efficient bifunctional electrocatalyst towards OER/ORR. (12th May 2023) - Liu, Xingmei; Fan, Liquan; Wang, Yuwei; Zhang, Weichao; Ai, Honglin; Wang, Ziteng; Zhang, Deqing; Jia, Hongge; Wang, Chaohui
Abstract: It is of significance to search non-noble metal OER/ORR catalysts with perfect performance. The introduction of carbon into perovskite can significantly enhance oxygen electrocatalytic activity. Herein, nanofiber-based Sm0.5 Sr0.5 Co0.2 Fe0.8 O3-δ /rGO (SSCF28/rGO) and Sm0.5 Sr0.5 Co0.2 Fe0.8 O3-δ /N-MWCNT (SSCF28/N-MWCNT) hybrids with various mass ratios were synthesized successfully by a facile ultrasonic mixing method and their oxygen evolution reaction (OER)/oxygen reduction reaction (ORR) properties were compared and studied. In 0.1 M KOH, SSCF28/N-MWCNT = 1.3 with optimal mass ratio shows better OER/OER bifuntional catalytic activity than SSCF28/rGO = 2:1. After 1000 CV cycles, SSCF28/N-MWCNT = 1.3 remains stable. Compared to SSCF28/rGO = 2:1, SSCF28/N-MWCNT = 1:3 shows promising practical applicability in metal-air batteries. The excellent OER/ORR activity of SSCF28/N-MWCNT = 1:3 can be attributed to the component optimization of perovskite and carbon and the synergistic effect between nanofiber-structured SSCF28 and N-functionalized MWCNT (N-MWCNT). Highlights: SSCF28/rGO and SSCF28/N-MWCNT were first synthesized via a facile method. SSCF28/N-MWCNT reveals a low overpotential of 53 mV in 0.1 M KOH. SSCF28/N-MWCNT shows excellent bifunctional activity with a low ΔE of 1.077 V. SSCF28/N-MWCNT has superior OER stability.